Development of a novel adaptive joining technology employing friction-spun joint connectors (FSJC) - Wiens, E.; Wischer, C.; Homberg, W. (ESAFORM)
Joints are an essential part of modern (lightweight) structures in a broad variety of applications. The reason for this is the rapidly increasing number of different material combinations needing to be joined in application areas like the automotive industry. It is currently common to use numerous auxiliary or standardized elements instead of individually adapted joining elements. This leads to a large number of different joining elements per product and thus to high costs. An innovative approach to overcoming this issue is the design, manufacture and setting of joint-specific joining elements. A good candidate for the manufacture of adapted joining elements of this type is the so-called friction spinning process. The joining elements formed in this way can be specifically adapted to the application in question in terms of both shape and mechanical properties. The part geometry required for the properties of a given joint is formed using a universal forming tool. This makes it possible to form a wide variety of sub geometries for the auxiliary joining part as a function of the prevailing joint condition, using a single forming tool and starting from the same semi-finished bar material. By applying different process strategies for the rotational speed and feed rate during the forming operation, the same part geometry can even be given different local mechanical properties. The following contribution presents the results of ongoing research work and includes the process concept, process properties, tooling and the results of experimental investigations into the joining of two sheet metal parts with help of this new joining process.

A First Approach for the Treatment of Galvanic Corrosion and of Load-Bearing Capacity of Clinched Joints - Harzheim, S.; Steinfelder, C.; Wallmersperger, T.; Brosius, A. (Key Engineering Materials)
Corrosion is a major cause for the failure of metallic components in various branches of the industry. Depending on the corrosion severity, the time until failure of the component varies. On the contrary, a study has shown that certain riveted metal joints, exposed to a short period of mechanical loading and corrosion, have greater fatigue limits. This study gives rise to the question how different corrosion exposure times affect joint metallic components. In the present research, a theoretical approach is developed in order to evaluate the influence of galvanic corrosion on joint integrity of clinched metal joints. At first, the framework for modeling galvanic corrosion is introduced. Furthermore, a simulative investigation of a clinching point is carried out based on the assumption that corrosion leads to a reduction of the contact area which leads to a local increase in contact pressure. For this purpose, the stiffness values of individual elements in a finite element model are reduced locally in the contact area of the undercut and the contact stress along a path is evaluated. Summarizing, a modeling approach is introduced to investigate corrosion effects on load-bearing behavior of clinched joints.

A finite plasticity gradient-damage model for sheet metals during forming and clinching - Friedlein, J.; Mergheim, J.; Steinmann, P. (Key Engineering Materials)
In recent years, clinching has gathered popularity to join sheets of different materials in industrial applications. The manufacturing process has some advantages, as reduced joining time, reduced costs, and the joints show good fatigue properties. To ensure the joint strength, reliable simulations of the material behaviour accounting for process-induced damage are expected to be beneficial to obtain credible values for the ultimate joint strength and its fatigue limit. A finite plasticity gradient-damage material model is outlined to describe the plastic and damage evolutions during the forming of sheet metals, later applied to clinching. The utilised gradient-enhancement cures the damage-induced localisation by introducing a global damage variable as an additional finite element field. Both, plasticity and damage are strongly coupled, but can, due to a dual-surface approach, evolve independently. The ability of the material model to predict damage in strongly deformed sheets, its flexibility and its regularization properties are illustrated by numerical examples.

Temperature dependent modelling of fibre-reinforced thermoplastic organo-sheet material for forming and joining process simulations - Gröger, B.; Hornig, A.; Hoog, A.; Gude, M. (Key Engineering Materials)
Joining and local forming processes for fibre-reinforced thermoplastics (FRTP) like hole-forming or variations of the clinching process require an in-depth understanding of the process induced effects on meso-scale. For numerical modelling with a geometrical description of a woven fabric, adequate material models for a representative unit cell are identified. Model calibration is achieved employing a mesoscopic finite-element-approach using the embedded element method based on tensile tests of the consolidated organo-sheets and a phenomenological evaluation of photomicrographs. The model takes temperature dependent stiffness and fibre tension failure into account.

A first Model of Fatigue Corrosion of a Metal through Hydrogen Embrittlement - Hofmann, M.; Shi, Y.; Wallmersperger, T. (PAMM)
Predicting the durability of components under mechanical loading combined with environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. Precise predictions are neccesary for lightweight design in transportation due to environmental protection. During corrosion often hydrogen is produced by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions leading to early and unexpected failure. Until now predictions are mostly done through costly experiments. In the present research, a first simple simulation model based on the fundamentals of electrochemistry and continuum damage mechanics is developed to couple the damage induced by the mechanical stress with the hydrogen embrittlement. Results of the durability are presented for the case of uniaxial cyclic loading for varying testing frequency.

Approach for the automated analysis of geometrical clinch joint characteristics - Zirngibl, C.; Schleich, B. (Key Engineering Materials)
Due to their cost-efficiency and environmental friendliness, the demand of mechanical joining processes is constantly rising. However, the dimensioning and design of joints and suitable processes are mainly based on expert knowledge and few experimental data. Therefore, the performance of numerical and experimental studies enables the generation of optimized joining geometries. However, the manual evaluation of the results of such studies is often highly time-consuming. As a novel solution, image segmentation and machine learning algorithm provide methods to automate the analysis process. Motivated by this, the paper presents an approach for the automated analysis of geometrical characteristics using clinching as an example.

Parametric FEM for computational homogenization of heterogeneous materials with random voids - Pivovarov, Dmytro; Mergheim, Julia; Willner, Kai; Steinmann, Paul (PAMM)
Computational homogenization is a powerful tool which allows to obtain homogenized properties of materials on the macroscale from the simulation of the underlying microstructure. The response of the microstructure is, however, strongly affected by variations in the microstructure geometry. The effect of geometry variations is even stronger in cases when the material exhibits plastic deformations. In this work we study a model of a steel alloy with arbitrary distributed elliptic voids. We model one single unit cell of the material containing one single void. The geometry of the void is not precisely known and is modeled as a variable orientation of an ellipse. Large deformations applied to the unit cell necessitate a finite elasto-plastic material model. Since the geometry variation is parameterized, we can utilize the method recently developed for stochastic problems but also applicable to all types of parametric problems — the isoparametric stochastic local FEM (SL-FEM). It is an ideal tool for problems with only a few parameters but strongly nonlinear dependency of the displacement fields on parameters. Simulations demonstrate a strong effect of parameter variation on the plastic strains and, thus, substantiate the use of the parametric computational homogenization approach.

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz Sebastian; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Influence of pin geometry on the joint strength of CFRT-metal hybrid parts with metallic pins - Popp, Julian; Kleffel, Tobias; Drummer, Dietmar (Joining Plastics)

Entwicklung einer Methode zur differenzierten Messung des Wachstums der Rissenden von Innenrissen mit der Elektropotentialmethode - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of rivet length on joint formation on self-piercing riveting process considering further process parameters - Kappe, Fabian; Bielak, Christian Roman; Sartisson, Vadim; Bobbert, Mathias; Meschut, Gerson (ESAFORM 2021)
Driven by the CO2-emission law by the European government and the increasing costs for raw materials as well as energy, the automotive industry is increasingly using multi-material constructions. This leads to a continuous increase in the use of mechanical joining techniques and especially the self-piercing riveting is of particular importance. The reason for this is the wide range of joining possibilities as well as the high load-bearing capacities of the joints. To be able to react to changing boundary conditions, like material thickness or strength variation of the sheets, research work is crucial with regard to the increase of versatility. In this paper, a numerical study of the influences on the selfpiercing riveting process is presented. For this purpose, the influence of different process parameters such as rivet length and die depth on various quality-relevant characteristics were investigated. With the help of the design of experiment, significant influences were determined and interactions between the individual parameters are shown.

Influence of various procedures for the determination of flow curves on the predictive accuracy of numerical simulations for mechanical joining processes - Böhnke, Max; Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Materials Testing)
The predictive quality of numerical simulations for mechanical joining processes depends on the implemented material model, especially regarding the plasticity of the joining parts. Therefore, experimental material characterization processes are conducted to determine the material properties of sheet metal and generate flow curves. In this regard, there are a number of procedures which are accompanied by varying experimental efforts. This paper presents various methods of determining flow curves for HCT590X as well as EN AW-6014, including varying specimen geometries and diverse hardening laws for extrapolation procedures. The flow curves thus generated are compared considering the variety of plastic strains occurring in mechanical joining processes. The material data generated are implemented in simulation models for the joining technologies, clinching and self-piercing riveting. The influence of the varied methods on the predictive accuracy of the simulation model is analysed. The evaluation of the differing flow curves is achieved by comparing the geometric formation of the joints and the required joining forces of the processes with experimentally investigated joints.

New Approach for Versatile Self Piercing Riveting: Joining System and Auxiliary Part - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
The increasing use of multi-material constructions lead to a continuous increase in the use of mechanical joining techniques due to the wide range of joining possibilities as well as the high load-bearing capacities of the joints. Nevertheless, the currently rigid tool systems are not able to react to changing boundary conditions, like changing the material-geometry-combination. Therefore research work is crucial with regard to versatile joining systems. In this paper, a new approach for a versatile self-piercing riveting process considering the joining system as well as the auxiliary joining part is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Investigation of the influence of varying tumbling strategies on a tumbling self-piercing riveting process - Wituschek, Simon; Kappe, Fabian; Lechner, Michael (Production Engineering)

Load Path Transmission in Joining Elements - Steinfelder, Christian; Martin, Sven; Brosius, Alexander; Tröster, Thomas (Key Engineering Materials)
The mechanical properties of joined structures are determined considerably by the chosen joining technology. With the aim of providing a method that enables a faster and more profound decision-making in the spatial distribution of joining points during product development, a new method for the load path analysis of joining points is presented. For an exemplary car body, the load type in the joining elements, i.e. pure tensile, shear and combined tensile-shear loads, is determined using finite element analysis (FEA). Based on the evaluated loads, the resulting load paths in selected joining points are analyzed using a 2D FE-model of a clinching point. State of the art methods for load path analysis are dependent on the selected coordinate system or the existing stress state. Thus, a general statement about the load transmission path is not possible at this time. Here, a novel method for the analysis of load paths is used, which is independent of the alignment of the analyzed geometry. The basic assumption of the new load path analysis method was confirmed by using a simple specimen with a square hole in different orientations. The results presented here show a possibility to display the load transmission path invariantly. In further steps, the method will be extended for 3D analysis and the investigation of more complex assemblies. The primary goal of this methodical approach is an even load distribution over the joining elements and the component. This will provide a basis for future design approaches aimed at reducing the number of joining elements in joined structures.

Joint point loadings in car bodies – the influence of manufacturing tolerances and scatter in material properties - Martin, Sven; Tröster, Thomas (ESAFORM 2021)

Joining with versatile joining elements formed by friction spinning - Wischer, Christian; Wiens, Eugen; Homberg, Werner (Journal of Advanced Joining Processes)